2017
DOI: 10.1175/jamc-d-16-0206.1
|View full text |Cite
|
Sign up to set email alerts
|

Using a Bayesian Regression Approach on Dual-Model Windstorm Simulations to Improve Wind Speed Prediction

Abstract: Weather prediction accuracy is very important given the devastating effects of extreme-weather events in recent years. Numerical weather prediction systems are used to build strategies to prevent catastrophic losses of human lives and the environment and have evolved with the use of multimodel or single-model ensembles and data-assimilation techniques in an attempt to improve the forecast skill. These techniques require increased computational power (thousands of CPUs) because of the number of model simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…BLR is implemented by combining 10 NCAR ensemble members, similar to the method applied in Yang et al () that combined output from two NWP models for a different set of historical storms than the ones considered herein. A Bayesian approach is used to deal with uncertainty of the unknown regression coefficients and variances for the ensemble members, and these unknown parameters are basically inferred to probabilistic forms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…BLR is implemented by combining 10 NCAR ensemble members, similar to the method applied in Yang et al () that combined output from two NWP models for a different set of historical storms than the ones considered herein. A Bayesian approach is used to deal with uncertainty of the unknown regression coefficients and variances for the ensemble members, and these unknown parameters are basically inferred to probabilistic forms.…”
Section: Methodsmentioning
confidence: 99%
“…We follow the assumption introduced by Yang et al () that the best postprocessed model will be the ensemble mean, indicated by a mean vector of μ β = [0 0.1…0.1]. If the prior variances ( σi2) are made smaller, the results will shrink toward this assumption.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ML model and statistical methods are based on myriad historical data not considering the meteorological conditions. Data-driven models are generally accepted as a feasible approach for establishing the capability for wind-speed predictions [24][25][26][27][28][29][30]. For instance, Li et al [31] proposed a data-driven model for determining the wind-power spectrum of a The numerical weather prediction (NWP) model is a method of weather simulation that employs a set of equations that describe the flow of fluids.…”
Section: Introductionmentioning
confidence: 99%